2012
DOI: 10.1590/s0100-29452012000200034
|View full text |Cite
|
Sign up to set email alerts
|

Quince 'CPP': new dwarf rootstock for pear trees on organic and high density planting

Abstract: ABSTRACT-In Brazil, pear production presents the same incipient situation over the last 15 years, due mostly to low production technology. In this context, this study aimed to evaluate the development, growth and production of the pear tree cultivars Cascatense, Tenra and Hosui grafted on 'CPP' quince rootstock, using 'FT' pear as interstem. This trial was carried out in Guarapuava, State of Paraná, Southern region of Brazil, by five productive cycles. The pear trees were planted in September of 2004, spaced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…'Abbé Fetel' and 'Conference' to be shown as cultivars with higher and similar acidity content as compared with 'Starking Delicious'. Great variations among cultivars for SSC and TA are previously reported (Botelho et al, 2012). Kiprijanovski and Ristevski (2009) noted that 'Conference' on quince BA.29 also contained higher level of soluble solids than 'Abbé Fetel' and 'Starking Delicious', whereas 'Starking Delicious' and 'Conference' had higher TA than 'Abbé Fetel', which confirmed our results, however, values for both SSC and TA in their study were much lower than our data.…”
Section: Fruit Chemical Compositionsupporting
confidence: 89%
See 3 more Smart Citations
“…'Abbé Fetel' and 'Conference' to be shown as cultivars with higher and similar acidity content as compared with 'Starking Delicious'. Great variations among cultivars for SSC and TA are previously reported (Botelho et al, 2012). Kiprijanovski and Ristevski (2009) noted that 'Conference' on quince BA.29 also contained higher level of soluble solids than 'Abbé Fetel' and 'Starking Delicious', whereas 'Starking Delicious' and 'Conference' had higher TA than 'Abbé Fetel', which confirmed our results, however, values for both SSC and TA in their study were much lower than our data.…”
Section: Fruit Chemical Compositionsupporting
confidence: 89%
“…It seems that early and high productivity of pear trees first of all depends on cultivar, rootstock and maiden tree quality (Sosna and Szewczuk 2006;Milošević and Milošević 2011), and also on environment (Sosna and Kortylewska 2012;Lepsis et al 2013), cultural practices, such as training and pruning system (Elkins and De Jong 2002;Vercammen 2002;Dierend and Bier-Kamotzke 2014) or fertilization and irrigation (Salem et al 2010;Dar et al 2012). Impact of planting distance on the cumulative yield was also previously obtained by Robinson (2011), being higher under higher density with group of quince rootstocks as compared to others (Iglesias et al 2004;Botelho et al 2012).…”
Section: Tree Size Precocity Yield and Yield Efficiencysupporting
confidence: 58%
See 2 more Smart Citations
“…monstrosa) is a strong dwarfing rootstock [ 84 ]. Quince rootstocks can induce dwarfism in pear trees, and quince ‘CPP’ was introduced as a new dwarf rootstock for pear cultivars [ 85 ]. Phenotyping vigour control in peach rootstock selections showed that xylem characteristics are associated with tree stature [ 86 ].…”
Section: Effects Of the Rootstock On Different Horticultural Traits I...mentioning
confidence: 99%